House dust mite sensitization and exposure affects bronchial epithelial anti‐microbial response to viral stimuli in patients with asthma. Issue 8 (11th February 2022) - Cerps, Samuel; Sverrild, Asger; Ramu, Sangeetha; Nieto‐Fontarigo, Juan José; Akbarshahi, Hamid; Menzel, Mandy; Andersson, Cecilia; Tillgren, Sofia; Hvidtfeldt, Morten; Porsbjerg, Celeste; Uller, Lena
Abstract: Introduction: Allergen exposure worsens viral‐triggered asthma exacerbations and could predispose the host to secondary bacterial infections. We have previously demonstrated that exposure to house dust mite (HDM) reduced TLR‐3‐induced IFN‐β in human bronchial epithelial cells (HBECs) from healthy donors. We hypothesize that HDM sensitization in different ways may be involved in both viral and bacterial resistance of HBECs in asthma. In this study, the role of HDM sensitization and effects of HDM exposure on viral stimulus‐challenged HBECs from asthmatic donors have been explored with regard to expression and release of molecules involved in anti‐viral and anti‐bacterial responses, respectively. Methods: HBECs from HDM‐sensitized (HDM+) and unsensitized (HDM‐) patients with asthma were used. HBECs were exposed to HDM or heat inactivated (hi)‐HDM (20 μg/ml) for 24 h prior to stimulation with the viral infection mimic, Poly(I:C), for 3 or 24 h. Samples were analyzed with ELISA and RT‐qPCR for β‐defensin‐2, IFN‐β, TSLP, and neutrophil‐recruiting mediators: IL‐8 and TNF‐⍺. NFκB signaling proteins p105, p65, and IκB‐⍺ were analyzed by Western blot. Results: Poly(I:C)‐induced IFN‐β expression was reduced in HBECs from HDM + compared to HDM‐ patients ( p  = 0.05). In vitro exposure of HBECs to HDM furthermore reduced anti‐microbial responses to Poly(I:C) including β‐defensin‐2, IL‐8, and TNF‐⍺, along with reduced NFκB activity. This was observed in HBECs from asthma patients sensitized to HDM, as well as in non‐sensitized patients. By contrast, Poly (I:C)‐induced release of TSLP, a driver of T2 inflammation, was not reduced with exposure to HDM. Conclusion: Using HBECs challenged with viral infection mimic, Poly(I:C), we demonstrated that allergic sensitization to HDM was associated with impaired anti‐viral immunity and that HDM exposure reduced anti‐viral and anti‐bacterial defense molecules, but not TSLP, across non‐allergic as well as allergic asthma. These data suggest a role of HDM in the pathogenesis of asthma exacerbations evoked by viral infections including sequential viral‐bacterial and viral‐viral infections. Abstract : In this study, we investigate the role of HDM sensitization and effects of HDM exposure on viral mimic‐challenged HBECs from asthmatic donors. In vitro exposure of viral mimic‐challenged HBECs to HDM reduces IFN‐β and anti‐microbial agents including β‐def‐2, IL‐8, and TNF‐α, but not TSLP, across non‐allergic as well as allergic asthma. Data suggest that both HDM sensitization and acute exposure to HDM contribute to reducing infection‐evoked immune protection in asthma and thus increase the risk of symptomatic infections and exacerbations.Abbreviations: β‐def‐2, β‐defensin‐2; HBECs, human bronchial epithelial cells; HDM, house dust mite; IFN‐β, interferon‐β; MDA‐5, melanoma differentiation‐associated protein; NF‐κB, nuclear factor‐kappa B; Poly (I:C), polyinosinic‐polycytidylic acid; RIG‐I, retinoic acid‐inducible gene I; TLSP, thymic stromal lymphopoietin